The Concept of Education in the UK - Anisa Oktaviana; Mohammad Alfarabi; Rizwan Rizwan; Ummi Hanifaa (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyse the education system in England using the library research method. The data used in this study come from various literature sources such as books, scientific journals, and official reports that discuss education policies, curriculum structures, and challenges faced by the English education system. The results of the study indicate that the education system in England has a well-structured curriculum that is oriented towards academic achievement and student skill development. However, there are significant challenges related to socio-economic disparities, which affect access to quality education and uneven adoption of technology. Based on these findings, this study suggests more inclusive policies and strengthening digital infrastructure to support the success of the education system in the future. This research is expected to contribute to the development of fairer and more equitable education in England.